2019
DOI: 10.1111/eci.13169
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate description of placebo and sham controls in a systematic review of recent trials

Abstract: Background Poorly described placebo/sham controls make it difficult to appraise active intervention benefits and harms. The 12‐item Template for Intervention Description and Replication (TIDieR) checklist was developed to improve the reporting of active interventions. The extent to which TIDieR has been used to improve description of placebo or sham control is not known. Materials and methods We systematically identified and examined all placebo/sham‐controlled randomised trials published in 2018 in the top si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This was usually not reported in the published article, or even worse, were misclassified as matching. Inadequate reporting of placebo controls was also found by Webster and colleagues, although not focusing on the reporting of matching [16].…”
Section: Discussionmentioning
confidence: 77%
“…This was usually not reported in the published article, or even worse, were misclassified as matching. Inadequate reporting of placebo controls was also found by Webster and colleagues, although not focusing on the reporting of matching [16].…”
Section: Discussionmentioning
confidence: 77%
“…These findings are comparable to recent studies evaluating intervention reporting. For example, Webster et al recently found that, on average, only 8 out of 12 TIDieR items were reported in placebo and sham-controlled trials published in the top six general medical journals 22. Another study found only 8.8/12 TIDieR items reported for poststroke exercise programme interventions 23…”
Section: Discussionmentioning
confidence: 99%
“…JH, TH, and RKW conducted preliminary research exploring the need to describe placebo and sham components adequately [2,3,19]. JH drafted and registered the protocol [20].…”
Section: Preliminary Researchmentioning
confidence: 99%
“…To address intervention reporting, the Template for Intervention Description and Replication (TIDieR) checklist was developed to aid reporting of interventions and can be used in conjunction with CONSORT. However, neither CONSORT nor TIDieR explicitly mention placebo or sham controls, and our background research revealed that they require some modification to guide adequate reporting of these interventions [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation